2006
DOI: 10.1097/01.fjc.0000211789.37658.e4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hypertension Induced by Nitric Oxide (NO) Deficiency: Focus on Venous Function

Abstract: Loss of endothelial cell-derived nitric oxide (NO) in hypertension is a hallmark of arterial dysfunction. Experimental hypertension created by the removal of NO, however, involves mechanisms in addition to decreased arterial vasodilator activity. These include augmented endothelin-1 (ET-1) release, increased sympathetic nervous system activity, and elevated tissue oxidative stress. We hypothesized that increased venous smooth muscle (venomotor) tone plays a role in Nomega-nitro-L-arginine (LNNA) hypertension t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 63 publications
1
12
0
1
Order By: Relevance
“…Acute inhibition of the SNS in this model has been shown to produce either a substantial fall or a small change in blood pressure, particularly in the initial phase of hypertension. However, a progressive increase in sympathetic tone was reported by others (8,20,21) . This discrepancy may be related to methodological reasons, such as the dose and duration of L-NAME treatment and the use of anesthesia.…”
Section: Vc Biancardi Et Almentioning
confidence: 97%
“…Acute inhibition of the SNS in this model has been shown to produce either a substantial fall or a small change in blood pressure, particularly in the initial phase of hypertension. However, a progressive increase in sympathetic tone was reported by others (8,20,21) . This discrepancy may be related to methodological reasons, such as the dose and duration of L-NAME treatment and the use of anesthesia.…”
Section: Vc Biancardi Et Almentioning
confidence: 97%
“…Various vasoactive compounds have been suggested as potential mechanisms for endothelial dysfunction in hypertension including endothelial-derived nitric oxide (NO) [14], endothelin-1 [15], and others. However, the focus of this article is on recently described mechanisms of endothelial dysfunction in obesity that are potentially mediated by leptin.…”
Section: Leptin and Endothelial Dysfunctionmentioning
confidence: 99%
“…When recorded, the HR was reduced with intravenous tempol in six of seven hypertensive rat models (Table 1, Studies in hypertensive rats with intravenous tempol ) including one study in which NOS was blocked (Thakali et al, 2006). Four studies in normotensive models reported a modest increase in HR with intravenous tempol (Table 1, Studies in normotensive rats with intravenous tempol ).…”
Section: Mechanistic Basis Of the Blood Pressure-lowering Effect mentioning
confidence: 99%